Project activity at the university: History and problems of application - Kokorina, Yulia; Vagabov, Makhach; Gorshkova, Tatyana; Lelina, Elena (Linguistics and Culture Review, 2021)
Project activity as a kind of pedagogical technology of higher education is widely used today in the world and in modern Russia. The optimal application of this method is impossible without the knowledge with its history, the experience of fellow teachers, and understanding the modern problems of educational design at the university. The beginning of the path of mastering this method in the world and in our country, a path that was sometimes difficult and ambiguous, is explored in this work. The propositions expressed by the first researchers in this field were developed by them within the framework of both higher and secondary schools. Therefore, this paper considers pedagogical technologies not only of higher, but also of secondary education. The purpose of this work is to identify the deep essence of project activity as a method, paying attention to the ideas that formed its basis, and modern problems.